Metformin May Contribute to Inter-individual Variability for Glycemic Responses to Exercise - Malin, Steven K.; Stewart, Nathan R. (Frontiers in Endocrinology, 2020)
Metformin and exercise independently improve glycemic control. Metformin traditionally is considered to reduce hepatic glucose production, while exercise training is thought to stimulate skeletal muscle glucose disposal. Collectively, combining treatments would lead to the anticipation for additive glucose regulatory effects. Herein, we discuss recent literature suggesting that metformin may inhibit, enhance or have no effect on exercise mediated benefits towards glucose regulation, with particular emphasis on insulin sensitivity. Importantly, we address issues surrounding the impact of metformin on exercise induced glycemic benefit across multiple insulin sensitive organs (e.g. skeletal muscle, liver, adipose, vasculature and the brain) in effort to illuminate potential sources of inter-individual glycemic variation. Therefore, the review identifies gaps in knowledge that require attention in order to optimize medical approaches that improve care of people with elevated blood glucose levels and are at risk of cardiovascular disease.